1995
DOI: 10.1046/j.1471-4159.1995.64010130.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Receptor‐Mediated Stimulation of Phosphoinositide Breakdown in Chick Brain Slices

Abstract: The direct effect of melatonin and related agonists on Li+‐amplified phosphoinositide breakdown was studied in chick brain slices prelabeled with myo‐[2‐3H]‐inositol. The melatonin receptor agonist 6‐chloromelatonin (10–100 µM) increased, in a concentration‐dependent manner, the accumulation of inositol phosphates (IP) in chick brain slices. This effect of 6‐chloromelatonin (10 µM) was rapid as transient increases in IP3/IP4 (maximal increase, 29% at 20 s) and IP2 levels (maximal increase, 36% at 1 min) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 38 publications
0
37
0
1
Order By: Relevance
“…In contrast to the uniform cAMP-dimishing effect of melatonin, both IP3-increasing [61,62] as well as IP3-decreasing [63,64] effects of melatonin have been described in different cell types. Previous studies in INS1 insulinoma cells indicated a dose-dependent stimulation of IP3 release by melatonin, while the competitive melatonin receptor antagonist luzindole was able to completely abolish such IP3-liberating effects of melatonin, thus giving strong evidence for the involvement of melatonin receptors [65] .…”
Section: Signal Transduction Of Melatonin Receptors In β-Cellsmentioning
confidence: 90%
“…In contrast to the uniform cAMP-dimishing effect of melatonin, both IP3-increasing [61,62] as well as IP3-decreasing [63,64] effects of melatonin have been described in different cell types. Previous studies in INS1 insulinoma cells indicated a dose-dependent stimulation of IP3 release by melatonin, while the competitive melatonin receptor antagonist luzindole was able to completely abolish such IP3-liberating effects of melatonin, thus giving strong evidence for the involvement of melatonin receptors [65] .…”
Section: Signal Transduction Of Melatonin Receptors In β-Cellsmentioning
confidence: 90%
“…After sonication (as described above) and centrifugation at 20,000 ϫ g for 15 min (4°C), the supernatants were extracted with water-saturated ether and neutralized with 1 M NH 4 HC O 3 . Ion exchange chromatography (Dowex AG 1-X8 resin, formate form; BioRad) of the samples was performed as described previously (Popova and Dubocovich, 1995). Total [ 3 H]inositol phosphates were quantified by liquid scintillation counting.…”
Section: Methodsmentioning
confidence: 99%
“…Endogenous phosphoinositide pools of SK-N-SH cells were prelabeled with myo-[ 3 H]inositol (Popova and Dubocovich, 1995), and carbachol-induced inositol phosphate generation was studied in colchicine-treated or control cells (Fig. 8).…”
Section: Microtubule Depolymerization Inhibits Phosphoinositide Hydromentioning
confidence: 99%
“…Melatonin and N-acetyl-serotonin (NAS) are thought to induce IP 3 generation in different systems such as hamster melanoma cells (17), pigeon brain (18), chick brain (19), and dinoflagellates (20). The ability of IP 3 to mobilize Ca 2+ from intracellular stores and therefore to trigger many biological processes such as cell division is well known (21).…”
Section: Introductionmentioning
confidence: 99%